Ocular effects of retrobulbar block with different local anesthetics in healthy dogs - Honsho, Cristiane dos Santos (2014)
The objective of this study was to evaluate the ocular effects, the feasibility and the quality of retrobulbar block using the inferior temporal technique with different local anesthetics applied with the Tuohy epidural needle in dogs. Eight dogs were included in the experiment and each one was studied four times, with interval of 15 days between the treatments: Lido -2% lidocaine, Ropi - 0.75% ropivacaine, Bupi - 0.5% racemic bupivacaine and Levo - 0.75% levobupivacaine. Except for the ropivacaine, all of the local anesthetics contained epinephrine at 1: 200.000. The blocks were performed in the right eyes immediately after anesthetic induction, and the left eyes were not blocked and were used as controls. The intraocular pressure, tear production and corneal sensitivity were evaluated before any procedure (T0), 30 min after premedication (TMPA), 30 min after anesthetic induction (T30), after recovery from anesthesia (TREC), every 60 min up to 360 min and 12 and 24 h after the block. The pupil diameter was evaluated at the same time points, excepted at T0. The maximum pupillary dilatation was observed in Lido group at T120 followed by Ropi at TREC, and Bupi and Levo at T30. All of the anesthetics maintained eye pressure within acceptable levels for normal dogs and significantly reduced tear production. Tear production returned earliest in group Lido, followed by Bupi, Ropi and Levo. The corneal sensitivity returned earliest in group Lido, followed by Ropi, Bupi and Levo. The retrobulbar block using the temporal inferior technique proved to be feasible and safe, although lubrication of the ocular surface is suggested.